Developing a core outcome set for Menière’s disease trials, the COSMED study: a scoping review on outcomes used in existing trials - Boreel, Maud M. E.; van Esch, Babette F.; van Beers, Maartje A.; Kaski, Diego; Bruintjes, Tjasse D.; van Benthem, Peter Paul G. (Frontiers in Neurology, 2025)
IntroductionMenière’s disease (MD) is an inner ear disorder characterized by episodic vertigo, fluctuating sensorineural hearing loss, tinnitus, and aural fullness. As of yet, the etiology of MD remains unknown, which contributes to the lack of an evidence-based treatment. Outcomes and outcome measurement instruments (OMIs) used in trials assessing the effectiveness of potential MD treatment are randomly selected due to the absence of established guidelines on this matter. The objective of this review is to give an overview of the outcome domains, outcomes and OMIs used in randomized controlled trials (RCTs) evaluating treatment effects in MD to 2024. This will be the first step of developing a Core Outcome Set (COS) for MD trials.MethodsA literature search of the PubMed, Embase and Cochrane library databases was conducted from inception to November 2024. All RCTs on the treatment effect of various therapies for patients suffering from MD were included. Among other details, we extracted and analyzed all outcome domains, outcomes, and OMIs used in these RCTs.ResultsA total of 76 RCTs were included, revealing a diverse range of outcomes and OMIs used across the included studies. Outcome domains encompassed dizziness, hearing, tinnitus, aural fullness, quality of life (QoL) and other. Outcomes used most frequently included: the severity of vertigo attacks, the number of vertigo attacks, vestibular function, hearing loss, severity of hearing loss, QoL related to dizziness, and Qol related to tinnitus. The latter two were most commonly measured with the Dizziness Handicap Inventory (DHI), the Functional Level Scale (FLS) and the Tinnitus Handicap Inventory (THI) respectively. For the other outcomes, there was little uniformity in the use of OMIs. Moreover, there was a notable lack of validated OMIs used in the included RCTs.ConclusionThis scoping review highlights the need for standardizing outcome selection for RCTs focusing on the treatment of MD. In this first step of developing a Core Outcome Set for MD, we identified a potential list of outcomes to be used in the next steps of ‘the Core Outcome Set for Menière’s Disease (COSMED)’ study.